Law and literature possibilities and perspectives - Ward, Ian 1963- (Cambridge University Press, 1995)
The emergence of an interdisciplinary study of law and literature is one of the most exciting theoretical developments taking place in North America and Britain. In Law and Literature: Possibilities and Perspectives Ian Ward explores the educative ambitions of the law and literature movement, and its already established critical, ethical and political potential. He reveals the law in literature, and the literature of law, in key areas of literature, from Shakespeare to Beatrix Potter to Umberto Eco, and from feminist literature to children's literature to the modern novel, drawing out the interaction between rape law and The Handmaid's Tale, and the psychology of English property law and The Tale of Peter Rabbit. This original book defines the developing state of law and literature studies, and demonstrates how the theory of law and literature can illuminate the literary text